2015
DOI: 10.1109/ted.2015.2421556
|View full text |Cite
|
Sign up to set email alerts
|

Modeling of Dynamic Operation of T-RAM Cells

Abstract: This paper presents a comprehensive simulation analysis of the dynamic operation of T-RAM cells. The analysis addresses the evolution of cell electrostatics and of carrier concentrations and flows in the device when the gate voltage undergoes a fast low-to-high switch, as required by both read and write operations. The results clarify, first of all, the basic physics making holes in the p-base the physical element allowing information storage in the device. From this starting point, the working principles expl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 8 publications
0
6
2
Order By: Relevance
“…From the carrier profiles in Fig. 3, contrary to the above conclusion ([3]- [6]), accumulation of holes is actually observed in the p-base, under the gate, for both memory states "1" (p ∼4.2x10 18 cm −3 ) and "0" (∼3.4x10 17 cm −3 ). This means that the physical memory mechanism cannot be the accumulation or depletion of holes in the base, under the gate, as claimed in [3]- [6].…”
Section: Resultscontrasting
confidence: 62%
See 2 more Smart Citations
“…From the carrier profiles in Fig. 3, contrary to the above conclusion ([3]- [6]), accumulation of holes is actually observed in the p-base, under the gate, for both memory states "1" (p ∼4.2x10 18 cm −3 ) and "0" (∼3.4x10 17 cm −3 ). This means that the physical memory mechanism cannot be the accumulation or depletion of holes in the base, under the gate, as claimed in [3]- [6].…”
Section: Resultscontrasting
confidence: 62%
“…The MOS gate provides capacitive coupling to the p-base of the TCCT, which enables switching speeds orders of magnitude faster than conventional thyristors [2]. A detailed investigation of the TRAM operation and design recently ([3]- [6]) concluded that "holes in the p-base under the gate represent the physical parameter determining the memory state of the cell" [5]: accumulation of holes for state "1", depletion of holes for state "0". The emphasis of these papers ([3]- [6]) was mainly on the process of the so called "dynamic sensing".…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As the illumination intensity increases from 0 to 1.5 mW cm −2 , the latch-up and latch-down voltages shift from 2.95 to 1.79 V and 1.84 to 1.17 V, respectively. The latch-up (or latch-down) voltage can be modulated by gatecontrolled carrier injection in the field-effect diodes [25,26], gated thyristors [27,28], Z 2 -FETs [21,29], and FBFETs [22,23]. It is worth noting that, instead of gate control, the potential barriers can be tuned using illumination.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, the impact ionization model, which induces the abrupt current flow, was not considered in this work. This model is not one of the important factors that can affect the operation of FBFET or the device utilizing the same principle [18,19,26].…”
Section: Device Structure and Simulationmentioning
confidence: 99%